Deteksi Boraks Pada Bakso Dagangan Kota Kupang dengan Menggunakan Reagen Curcumax - Laha, Putri; Malelak, Gemini E. M.; Sulmiyati, Sulmiyati; Sipahelut, Geertruida M. (Animal Agricultura, 2024)
Borax is a chemical that is dangerous to public health but is often used in meatballs. This research aims to determine the presence of borax in meatballs sold in Kupang City by testing them using Curcumax reagent which is made from turmeric. This is done by testing 1 ml of meatball extract with 1 ml of Curcumax reagent, organoleptics observed in the form of color, aroma, texture and taste, durability test. Storage of meatballs in open and closed containers was observed every 24 hours for 5 days as a confirmation test to confirm the detection of borax content and a cooking loss test with boiling treatment for 15 minutes. Parametric data were analyzed using the Independent-samples T Test, organoleptic non-parametric data were analyzed using the Mann-Whitney test. The research results showed that of the 25 samples there were 5 test samples that were positive for borax. The conclusion regarding the qualitative assessment of the presence of borax was based on the color change of the meatball extract which changed from yellow to orange and brownish red. Meanwhile, the organoleptic results and cooking losses had no significant effect/were not significantly different (P>0.05).